Identification of the Wnt signaling activator leucine-rich repeat in Flightless interaction protein 2 by a genome-wide functional analysis - Liu, Jun (National Academy of Sciences, 2005)
The Wnt signaling pathway acts ubiquitously in metazoans to control various aspects of embryonic development. Wnt ligands bind their receptors Frizzled and low-density lipoprotein receptor-related protein 5/6 and function through Disheveled (Dvl), Axin, adenomatous polyposis coli, glycogen synthase kinase 3β, and casein kinase (CK) 1 to stabilize β-catenin and induce lymphocyte enhancer-binding factor (LEF)/T cell factor (TCF)-dependent transcriptional activities. To identify previously unrecognized Wnt signaling modulators, a genome-wide functional screen was performed using large-scale arrayed cDNA collections. From this screen, both known components and previously uncharacterized regulators of this pathway were identified, including β-catenin, Dvl1, Dvl3, Fbxw-1, Cul1, CK1ε, CK1δ, and γ-catenin. In particular, a previously unrecognized activator, LRRFIP2 (leucine-rich repeat in Flightless interaction protein 2), was found that interacts with Dvl to increase the cellular levels of β-catenin and activate β-catenin/LEF/TCF-dependent transcriptional activity. The function of LRRFIP2 is blocked when a dominant negative Dvl (Xdd1) is coexpressed. Expression of LRRFIP2 in Xenopus embryos induced double axis formation and Wnt target gene expression; a dominant negative form of LRRFIP2 suppresses ectopic Wnt signaling in Xenopus embryos and partially inhibits endogenous dorsal axis formation. These data suggest that LRRFIP2 plays an important role in transducing Wnt signals.